2010
DOI: 10.2304/elea.2010.7.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Gamers as Designers: A Framework for Investigating Design in Gaming Affinity Spaces

Abstract: This article addresses recent approaches to uncovering and theorizing the design activities that occur in online gaming affinity spaces. Examples are presented of productive d/Discourse present within online forums around three video game series, video games, or game platforms, and key design practices engaged upon by gamers in these spaces. It is argued that these activities are, in part, consequences of the affordances and constraints of the games under discussion. Repurposing the 'narratology vs. ludology' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…The study examined how cognitive functions were stretched across students' roles, practices, and resources. To understand modders' design activities, Duncan (2010) analyzed productive d/Discourse in the online discussion forums. Drawing on the concept of the “affinity space” and the “participatory culture,” the author viewed the online community through the lens of gamers as designers.…”
Section: Learning Beyond Gamingmentioning
confidence: 99%
“…The study examined how cognitive functions were stretched across students' roles, practices, and resources. To understand modders' design activities, Duncan (2010) analyzed productive d/Discourse in the online discussion forums. Drawing on the concept of the “affinity space” and the “participatory culture,” the author viewed the online community through the lens of gamers as designers.…”
Section: Learning Beyond Gamingmentioning
confidence: 99%
“…Previous studies of SDL in classroom environments showed that students were more motivated but also worried that they may have been missing important parts of the subject matter [5]. Other work has focused on the characteristics and effectiveness of online affinity spaces that lead to SDL and how to measure the learning that was occurring in these spaces [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the majority of studies about social interaction in MMOGs building upon this work have remained focused on interactions between strangers, or on how social interactions within the gameworld allow for the creation of friendship groups outside of one's immediate geographical area. Gee (2005) and others (Duncan, 2010;Hayes & Duncan, 2012) have explored how an opportunity to discuss shared interests can act as an "affinity space", where what brings people together is a common endeavor -in this case -a shared interest in a particular game. Researchers have also investigated the way gamemediated relationships may become romantic in nature, such as the work of Ferdig and Pytas (2012).…”
Section: Playing Mmogs As a Romantic Couple: A Review Of The Literaturementioning
confidence: 99%